The US and the Kurds, a Cold War story? - Campello, Maria Raphaela (Temporalidades, 2020)
This work was based on extensive historical research undertaken about the Kurdish peoples of Iraq and their relationship with the United Kingdom and the United States of America during the twentieth century. We seek to tension the reading of the Kurdish issue and its relationship with the United States as a Cold War story through a long-term perspective.